Distribution of Joint Assets For Divorced Wife in Unrecorded Marriage (Bima District) - Muh Asad Imaduddin; Rahmawati Rahmawati; Jufrin Jufrin (Jurnal Pendidikan Tambusai, 2022)
The practice of undisputed marriages is the same in the case of breaking up of marital relations and has implications for the process of dividing joint assets.So the purpose of this study is how the legal consequences and provisions for the distribution of assets for divorced wives from marriage are not recorded in the distribution of joint assets in civil law and how legal remedies for wives for the right to share joint assets for divorced wives in marriage are not recorded in Bima Regency.This study uses empirical legal research, with a Case Approach, a legal approach (approach status) and a conceptual approach (conceptual approach) using primary data, data analysis using qualitative descriptive with inductive thinking. The results of this study indicate that first a marriage is valid if it is carried out according to religious law and consecutive beliefs.Second, if the marriage is not registered, then it is not and the validity of the marriage, both in the distribution of joint property or gonorrhea property. Third, the legal consequences of unregistered marriages on the position of joint assets, marriages without official documents or commonly referred to as unregistered marriages,so that in the position of joint property the State is not entitled to regulate the distribution because it is not recorded in the marriage registration, but in the distribution of joint property it can still be carried out on condition that an agreement is made in the distribution of its assets.